PERANCANGAN STRATEGI DESAIN KOMUNIKASI VISUAL SEBAGAI BRAND DEVELOPMENT UNTUK TOPER GRAPHIC STUDIO - Christopher Chandra; Ferryanto Chia (Universitas Ciputra Surabaya, 2016)
Most design companies requires a rather expensive budget to design a brand and it also does not have transparent work structure. Which most of startup companies do not have a sufficent financial to do so and they also need a transparent work structure to inform them how will their design will be made. Thus, the purpose of this study is to form a business that is able to answer those needs. By using a qualitative research methods, which is interviewing two startup business owners. The result is to form a design company with a clear pricing structure and clear SOPs.